Water resistance and biodegradation properties of conventionally-heated and microwave-cured cross-linked cellulose nanocrystal/chitosan composite films. (June 2021) - Gan, Pei Gie; Sam, Sung Ting; Abdullah, M.F.; Omar, Mohd Firdaus; Tan, Wai Kian
Highlights: Conventionally-heated and microwave-cured glutaraldehyde crosslinked cellulose nanocrystals (CNC)/chitosan composite films were developed. The water vapor permeability, swelling property, film solubility and weight loss of chitosan composite films decreased with the addition of CNC and glutaraldehyde. Microwave-cured composite films exhibited lower water vapor permeability, swelling property, film solubility and weight loss compared to conventionally-heated composite films. Ophiocordyceps heteropoda, Enterobacter kobei and E. roggenkampii were firstly reported as the chitosan composite films-degrading microorganisms. Abstract: The cross-linking of cellulose nanocrystals (CNC)/chitosan composite films with glutaraldehyde (GA) as the cross-linking agent, was carried out by using conventional heating and microwave curing, respectively. The addition of 5 wt% CNC has significantly reduced the water vapor permeability (WVP) of chitosan films by 30% compared to the neat chitosan film. The decline in the swelling and solubility were also observed in the CNC/chitosan composite films. Moreover, the cross-linking has further enhanced the water resistance by reducing the WVP, swelling and solubility of CNC/chitosan films, especially for microwave-cured GA-cross-linked CNC/chitosan films. The biodegradation testing was performed by the soil burial experiment. The cross-linked chitosan composite films were found to have a lower degradability rate compared with the uncross-linked composites especially for the microwave-cured CNC/chitosan composite films. The composite films-degrading microorganisms were identified as Ophiocordyceps heteropoda, Enterobacter kobei and E. roggenkampii, by the molecular analysis via polymerase chain reaction and DNA sequencing. This study demonstrated that the CNC/chitosan composite films especially microwave-cured composite films could be the suitable materials to be employed as the food packaging with outstanding water resistance property and moderate biodegradability.